Developing a Canadian Indo-Pacific geopolitical orientation. (December 2021) - MacDonald, Adam; Vance, Carter
There is growing consensus that Canada needs to "do more" in the Indo-Pacific region as it becomes the centre of gravity in a changing international landscape—a landscape challenging several traditional assumptions about the nature and configuration of global power which Canadian foreign policy has rested upon for decades, specifically due to the emergence of Sino-American rivalry. It is clear Canada needs a regional approach which is rooted in and better informed by geopolitical considerations, but there remains an absence of analytical frameworks to compare and evaluate alternative approaches. In addressing this void, this paper sketches out and compares four possible orientations Canada could pursue towards the Indo-Pacific region: Minimal Engagement, US-Aligned Confrontation, Regional Multilateralism, and Selective Minilateralism. Remaining agnostic about which one(s) Canada should choose, the paper is designed to highlight the stark trade-offs Canada must increasingly confront as it navigates this uncertain environment.